The shape of utopia : the architecture of radical reform in nineteenth-century America - Cheng, Irene (Irene Chun-I) (Buell Center books in the history and theory of American architecture., 2023)
"The Shape of Utopia documents a pivotal moment in American history when ordinary people ardently believed in the potential to reshape society. Highlighting the inherent political capacity of architecture, Irene Cheng showcases how visionary utopian planners in the mid-nineteenth century used their blueprints as persuasive visual rhetoric that could mobilize others to share in their aspirations for a better world"--